Perancangan dan Evaluasi Lengan Robot 4-DOF Berbasis ESP32 Dengan Kendali Manual Menggunakan Aplikasi Bluetooth Android - Deswen Lumban Gaol; Michael Oklando Sihotang; Albert Sebastian Siahaan; Eka Dodi Suryanto; Dian Putra Saragi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of robotics and embedded systems has increased the need for accessible learning media to support the understanding of basic control concepts. However, industrial robotic systems are generally expensive and complex, making them less suitable for introductory learning. This study aims to design and evaluate a 4-degree-of-freedom (4-DOF) robotic arm based on ESP32 as a learning medium for basic control systems. The research method includes hardware and software system design, implementation of a Bluetooth-based control system using an Android gamepad interface, and experimental testing. The system applies an incremental control method combined with a Degree of Freedom mechanism to regulate actuator movement gradually. The evaluation covers control mapping accuracy, system responsiveness, angle constraints, startup stability, serial monitoring, and response consistency. The results show that the system successfully executes all control commands with accurate input-output mapping and stable performance. The system maintains actuator movement within safe angle limits and operates without disturbance during startup. In addition, the serial monitoring feature enables real-time visualization of the control process. The findings indicate that the developed system is suitable as a low-cost educational platform for learning basic robotic control concepts due to its simplicity, intuitiveness, and ease of implementation.